Nonrandom duplication of the chromosome bearing a mutated Ha-ras-1 allele in mouse skin tumors. - Bianchi, A B (1990)
We analyzed the normal/mutated allelic ratio of the Ha-ras-1 gene in mouse skin squamous cell carcinomas induced by initiation with dimethylbenz[a]anthracene and promotion with phorbol 12-myristate 13-acetate. DNA for these studies was obtained from short-term tumor cultures (24-72 hr) to eliminate the contribution of stromal and inflammatory cells to the sample. The allelotypic analysis was performed in 25 squamous cell carcinomas by quantitative radio-analysis of the Xba I restriction fragment length polymorphism as detected by BS9, a v-Ha-ras probe, and rehybridization of the Southern blots with probes for chromosomes 7 and 8. Approximately 85% of the tumors presented overrepresentation of the mutated allele in the form of 1 normal/2 mutated (12 tumors), 0 normal/3 mutated (4 tumors), 0 normal/2 mutated (3 tumors), and gene amplification (3 tumors). No tumor was found with a 2 normal/1 mutated allelic ratio. These results support our previous cytogenetic studies, indicating that trisomy of chromosome 7 is present in the majority of these tumors and show that nonrandom duplication of the chromosome carrying the mutated Ha-ras-1 allele appears to be a major mechanism by which the mutated gene is overrepresented.